PENGOLAHAN GEOLOKASI PRODUK DATA GAS RUMAH KACA (GRK) DARI SATELIT SUOMI NPP ATMS DAN CRIS DENGAN METODE INTERPOLASI RADIAL BASIS FUNCTION - Indradjad, Andy; Dyatmika, Haris Suka; Salyasari, Noriandini Dewi; Fibriawati, Liana; Indriani, Masnita (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2018)
Geolocation processing to produce spatial greenhouse gases data products consisting of CH4, CO2 and N20 gases has been carried out systematically. The greenhouse gases data are derived from Enviomental Data Record (EDR) Suomi NPP Satellite CrIS and ATMS Sensor products. During this process, there is an obstacle while performing the information data of greenhouse gases concentrations, due to the result of systematic processing files from EDR are still in netcdf format, so that it could not be distributed to users as they expected. The unique of unlimited netcdf format is that, it displays only numeric values with irregular resolution, unregistered and incompatible with commonly processing data software. This research aims to produce geolocation processing module in order to provide information of greenhouse gases data spatially by using coordinate pixel registration method into image data, convert Digital Number (DN) value with scale corresponding to Indonesian region and interpolation value between pixels with Radial Basis Function (RBF) method using linear function. The result from the geolocation processing module of greenhouse gases data product are concentration information from some altitude level. The product is in geotiff format with 50 km spasial resolusion.